Photonic Potentiation and Electric Habituation in Ultrathin Memristive Synapses Based on Monolayer MoS2. Issue 15 (5th March 2018) - He, Hui‐Kai; Yang, Rui; Zhou, Wen; Huang, He‐Ming; Xiong, Jue; Gan, Lin; Zhai, Tian‐You; Guo, Xin
Abstract: Monolayer of 2D transition metal dichalcogenides, with a thickness of less than 1 nm, paves a feasible path to the development of ultrathin memristive synapses, to fulfill the requirements for constructing large‐scale high density 3D stacking neuromorphic chips. Herein, memristive devices based on monolayer n‐MoS2 on p‐Si substrate with a large self‐rectification ratio, exhibiting photonic potentiation and electric habituation, are successfully fabricated. Versatile synaptic neuromorphic functions, such as potentiation/habituation, short‐term/long‐term plasticity, and paired‐pulse facilitation, are successfully mimicked based on the inherent persistent photoconductivity performance and the volatile resistive switching behavior. These findings demonstrate the potential applications of ultrathin transition metal dichalcogenides for memristive synapses. These memristive synapses with the combination of photonic and electric neuromorphic functions have prospective in the applications of synthetic retinas and optoelectronic interfaces for integrated photonic circuits based on mixed‐mode electro‐optical operation. Abstract : Synergetic optical and electrical neuromorphic functions are demonstrated in the memristive synapses based on monolayer MoS2 . These ultrathin artificial synapses with the behavior of photonic potentiation and electric habituation have prospective in the applications of synthetic retinas and optoelectronic interfaces for integrated photonic circuits based on the mixed electro‐optical operation.